2014
DOI: 10.1590/s1413-70542014000200002
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes in an oxisol treated with pyroligneous acid

Abstract: The use of pyroligneous acid (PA), a by-product of charcoal production, is an ancient practice applied in agriculture to control soil and plant pests and diseases. However, little is known about the chemical alterations that this product may cause on treated soil. Thus, the present work aimed to evaluate the effect of PA concentrations on soil ions movement and to verify possible soil chemical properties changes. Detachable columns were filled with Oxisol, submitted to application of 5 PA concentrations (0, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Due to its antimicrobial activity, PL also has been used for veterinary and agricultural purposes. It has a fertilizing effect on some plants and presents nematocidal, fungicidal, and insecticidal action in the control of pests and plant diseases, and the remediation of soils (Silva and Rodrigues 2014;Silva et al 2017;Theapparat et al 2015;Togoro et al 2014). Melo et al (2017) found promising results in using pyroligneous liquor for the integrated management of plant diseases.…”
Section: Responsible Editor: Giovanni Benellimentioning
confidence: 99%
“…Due to its antimicrobial activity, PL also has been used for veterinary and agricultural purposes. It has a fertilizing effect on some plants and presents nematocidal, fungicidal, and insecticidal action in the control of pests and plant diseases, and the remediation of soils (Silva and Rodrigues 2014;Silva et al 2017;Theapparat et al 2015;Togoro et al 2014). Melo et al (2017) found promising results in using pyroligneous liquor for the integrated management of plant diseases.…”
Section: Responsible Editor: Giovanni Benellimentioning
confidence: 99%
“…Agricultural uses of PA date back to the 1930s in Japan, when the product started to be applied as an antifungal and antibacterial agent on crops [ 12 ]. A large number of papers and technical reports show the undeniable efficiency of PA for soil conditioning [ 14 , 15 , 16 ] and for pest control in pure form or combined with conventional pesticides [ 4 , 12 , 17 , 18 ]. Additionally, PA has been successfully used to control fungal and bacterial diseases in plants [ 14 , 19 ] and as a herbicide [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of papers and technical reports show the undeniable efficiency of PA for soil conditioning [ 14 , 15 , 16 ] and for pest control in pure form or combined with conventional pesticides [ 4 , 12 , 17 , 18 ]. Additionally, PA has been successfully used to control fungal and bacterial diseases in plants [ 14 , 19 ] and as a herbicide [ 16 ]. Finally, PA is used as a plant growth enhancer, significantly stimulating the development of roots, stems, leaves, flowers, tubers and fruits, and also improving the sweet taste of fruits [ 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The following effects and properties are reported: soil conditioning; favouring the development of microbiota (Yoshimoto ; Steiner ; Togoro et al . ); use of plant pest control and management, pure (Tiilikkala et al . ) or in combination with conventional pesticides (Busoli et al .…”
Section: Introductionmentioning
confidence: 99%
“…PA has been well established for agricultural use in Japan and China since the 1930 decade (Tiilikkala et al 2010). The following effects and properties are reported: soil conditioning; favouring the development of microbiota (Yoshimoto 1994;Steiner 2008;Togoro et al 2014); use of plant pest control and management, pure (Tiilikkala et al 2010) or in combination with conventional pesticides (Busoli et al 2004;Thuler et al 2007;Kim et al 2008); appliance of PA in plant diseases caused by bacteria or fungus (Yoshimoto 1994;Jung, 2007;Payamara 2011). Also, the use of PA is cited as a plant growth enhancer, stimulating significantly the development of roots, stems, leaves, flower, tubers and fruits; and likewise improving the sweet taste of the latter (Yoshimoto 1994;Zulkarami et al 2011;Kang et al 2012); and moreover as a herbicide (Tiilikkala et al 2010).…”
Section: Introductionmentioning
confidence: 99%